2016
DOI: 10.1002/aenm.201600278
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanomaterials in Different Dimensions for Electrochemical Energy Storage

Abstract: In spite of an ongoing advancement, current popular EES systems including Li-ion batteries (LIBs), supercapacitors (SCs), and redox flow cells (RFCs) are limited by severe performance challenges of electrode materials in terms of low energy and power density as well as short durability. To mitigate the issues, carbon nanomaterials could be introduced to these EES systems, taking advantage of their unique geometry, excellent conductivity, large surface area, and intrinsic flexibility. Numerous carbon nanomateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(117 citation statements)
references
References 216 publications
(429 reference statements)
0
109
0
Order By: Relevance
“…Fortunately,p otassium alloys are better anode materials for potassium batteries. KPF 6 and KTFSI fail to sustain long-terms tability,w hereas KFSI enables highly reversible potassium plating/stripping electrochemistry.T hrough XPS and 1 Ha nd 19 FNMR spectroscopy investigations, they found that both KF and DME decomposition products formed the SEI layer.T hese components all contribute to the well-passivated potassium surface, and hence,l ead to ah ighly reversible cycle performance. Nevertheless, pure potassium anodesa re reported in the literatures for use in room-temperature potassium batteries, [17,[30][31][32] potassium-O 2 batteries, [33] and potassium-sulfur batteries.…”
Section: Potassiummentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately,p otassium alloys are better anode materials for potassium batteries. KPF 6 and KTFSI fail to sustain long-terms tability,w hereas KFSI enables highly reversible potassium plating/stripping electrochemistry.T hrough XPS and 1 Ha nd 19 FNMR spectroscopy investigations, they found that both KF and DME decomposition products formed the SEI layer.T hese components all contribute to the well-passivated potassium surface, and hence,l ead to ah ighly reversible cycle performance. Nevertheless, pure potassium anodesa re reported in the literatures for use in room-temperature potassium batteries, [17,[30][31][32] potassium-O 2 batteries, [33] and potassium-sulfur batteries.…”
Section: Potassiummentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In 1991, the commercialization of the lithium-ion battery (LIB) opened the door to high energy density storage of electricity. At the same time, human beings have lookedf or efficient energy-storage methods.…”
Section: Introductionmentioning
confidence: 99%
“…Among the available energy storage technologies 710 , battery is the best choice to store electricity in the form of chemical energy when considering the flexibility, convenience and energy conversion efficiency of device 1113 . Lithium ion batteries have been studied most commonly as rechargeable batteries 14–18 and magnesium ion batteries 19, 20 , zinc ion batteries 21, 22 and aluminium ion batteries 23 have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs have a tubular structure, showing a much high length‐to‐diameter ratio, typically several nanometers in diameter and many micrometers in length. Due to remarkable electroconductibility and large specific surface area, CNTs is supported to be a perfect conductive substrate for manganese‐based materials . Kang et al synthesized the MnO 2 nanorod/acid‐treated α‐CNT composites by coprecipitation way (Figure A), which displayed both excellent storage properties of 665 mAh/g at 0.1 A/g (400 mAh/g at 1A/g) and reversibility at various current rates (Figure B, C).…”
Section: The Strategies Of Performance Optimization For Manganese‐basmentioning
confidence: 99%